Application of Printable ITO/PEDOT Nanocomposites as Transparent Electrodes in Optoelectronic Devices - Maksimenko, Ilja; Kilian, Daniel; Mehringer, Christian; Voigt, Michael; Peukert, Wolfgang; Wellmann, Peter (Conference on Lasers and Electro-Optics, 2012)
Printable transparent hybrid composites consisting of indium tin oxide (ITO) nanoparticles and conducting polymer 3,4-polyethylenedioxythiophene: polystyrene sulfonic acid (PEDOT:PSS)) as matrix material were developed and used as transparent electrodes in all-printed flexible electroluminescent lamps and electrochromic display
Keywords: optical devices; electro-optical devices; thin films; transparent conductive coatings

Conductance Enhancement Mechanisms of Printable Nanoparticulate Indium Tin Oxide (ITO) Layers for Application in Organic Electronic Devices - Groß, Michael; Linse, Nicolas; Maksimenko, Ilja; Wellmann, Peter (Advanced Engineering Materials, 2009)
Keywords: ITO; nanoparticultae layers; conductance; infiltration

Conductance Enhancement of Nano-Particulate Indium Tin Oxide Layers Fabricated by Printing Technique - Groß, Michael; Maksimenko, Ilja; Faber, Hendrik; Linse, N.; Wellmann, Peter (Nanotech 2008, Vol. 1-3, 2008)
To understand the mechanisms behind the conductance improvement and to fathom the limits we did some investigations: long-term resistance measurements gave an insight in oxygen vacancy balance concentration. From infrared absorption measurements we inferred the free charge carrier density and at present we carry out XPS measurements which yield information about the alteration of oxygen vacancy concentration. Considering these data we discuss two conductance improving mechanisms: The increase of the free charge carrier density by a rise of oxygen vacancy concentration as well as a release of trapped charge carriers from the aggregate surface
Keywords: ITO; nanoparticles; transmittance; conductance

Conductivity and adhesion enhancement in low-temperature processed indium tin oxide/polymer nanocomposites - Maksimenko, Ilja; Groß, Michael; Königer, Tobias; Münstedt, Helmut; Wellmann, Peter (Thin Solid Films, 2010)
We report on the conductivity and adhesion enhancement of indium tin oxide (In(2)O(3):Sn; ITO) nanoparticle films by the application of polymers as matrix material. We fabricated ITO layers at a maximum process temperature of 130 degrees C by modifying and spin-coating nanoparticulate ITO dispersions. Dispersions containing the organic film-forming agent polyvinylpyrrolidone (PVP) and the organofunctional coupling agent 3-methacryloxypropyltrimethoxysilane (MPTS) have been developed to obtain transparent and conducting coatings on substrates which do not withstand high process temperatures like polymers or already processed glasses. The layers were cured by UV-irradiation as well as by low-temperature heat treatment (T = 130 degrees C) in air and under forming gas atmosphere (N(2)/H(2)). The influence of the additives on the electrical, optical, morphological and mechanical layer properties is reported. Compared to best pure ITO layers (3.1 Omega(-1)cm(-1)), the ITO-MPTS-PVP nanocomposite coatings exhibit a conductance of 9.8 Omega(-1)cm(-1). Stable sheet resistances of 750 Omega/square at a coexistent transmittance of 86% at 550 nm for a layer thickness of about 1.3 mu m were achieved. The conductance enhancement is a consequence of the consolidation of the ITO nanoparticle network due to the acting shrinkage forces caused either by drying in the case of PVP or UV-irradiation induced condensation and polymerization reactions in the case of MPTS. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Indium tin oxide (ITO); Nanoparticles; Polyvinylpyrrolidone (PVP); 3-Methacryloxypropyltrimethoxysilane (MPTS); Nanocomposite; Adhesion

Fabrication, charge carrier transport, and application of printable nanocomposites based on indium tin oxide nanoparticles and conducting polymer 3,4-ethylenedioxythiophene/polystyrene sulfonic acid - Maksimenko, Ilja; Kilian, Daniel; Mehringer, Christian; Voigt, Michael; Peukert, Wolfgang; Wellmann, Peter (Journal of Applied Physics, 2011)
Printable transparent hybrid composites consisting of indium tin oxide (In2O3:Sn; ITO) nanoparticles and conducting polymer 3,4-polyethylenedioxythiophene (PEDOT) as matrix material were developed. The basic idea is to fill up the pores of the highly porous nanoparticulate ITO network to improve the interparticle contact and hence the conductivity of printed ITO thin films. Ready-to-use and stable aqueous dispersions were fabricated starting from ITO nanoparticles and aqueous formulation of conducting PEDOT and polystyrene sulfonic acid (PSS). This report presents and discusses key factors to obtain stable ITO-PEDOT dispersions with different mixing ratios and their application for printable devices as transparent electrode material. It was found that the f-potential value is crucial for preparation of stable dispersions. Electrical and optical properties of the hybrid ITO-PEDOT coatings were analyzed. Temperature dependent resistivity measurements reveal that conduction occurs by fluctuation induced tunneling. Transparent and conducting nanocomposite layers with a conductivity as high as 132 X1cm1 were fabricated by a low-temperature (T¼130 C) and entirely vacuum-free process. An all-printed electroluminescent lamp on a flexible substrate was realized as a demonstrator showing the applicability of such coatings for voltage-driven optoelectronic devices.<br

Low temperature processing of hybrid nanoparticulate Indium Tin Oxide (ITO) polymer layers and application in large scale lighting devices - Maksimenko, Ilja; Wellmann, Peter (Thin Solid Films, 2011)
We report on transparent conductive indium tin oxide (In(2)O(3):Sn; ITO) nanoparticle films processed at a low temperature of 130 degrees C for the application in lighting devices using spin coating and doctor blading techniques. Major emphasis is put on the beneficial application of the particular transparent electrode material for the fabrication of patterned large area electroluminescence lamps. In order to improve film properties like adhesion and conductivity, hybrid nanoparticle-polymer blends out of ITO particles and organic film-forming agent polyvinylpyrrolidone (PVP) and the organofunctional coupling agent 3-methacryloxypropyltrimethoxysilane (MPTS) have been developed. The layers were cured by UV-irradiation, which was also used for lateral structuring of the transparent, conductive electrode. Additional low-temperature heat treatment (T = 130 degrees C) in air and forming gas improved the electronic properties. While pure ITO nanoparticulate layers processed at 130 degrees C exhibited conductance of up to 3.1 Omega(-1) cm(-1), the nanocomposite coatings showed a conductance of up to 9.8 Omega(-1) cm(-1). Corresponding layers with a sheet resistance of 750 Omega/square were applied in electroluminescent lamps. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: TCO (transparent conducting oxide); ITO (indium tin oxide); lighting; electroluminescence lamp

Low-temperature processing of transparent conductive indium tin oxide nanocomposites using polyvinyl derivatives - Maksimenko, Ilja; Wellmann, Peter (Thin Solid Films, 2011)
We report on the influence of additives on the electrical, optical, morphological and mechanical properties of transparent conductive indium tin oxide (In2O3:Sn; ITO) nanoparticle films by the use of polymers as matrix material. Key issues to fabricate layers suitable for use in electronic device applications are presented. Polyvinyl derivatives polyvinyl acetate, polyvinyl alcohol (PVA) and polyvinyl butyral were applied and their suitability to form transparent conductive ITO nanocomposite coatings at a maximum process temperature of 130 degrees C was investigated. A low-temperature treatment with UV-light has been developed to provide the possibility of curing ITO thin films deposited on substrates which do not withstand high process temperatures. Compared to best pure ITO layers (0.2 Omega(-1) cm(-1)), the ITO-PVA nanocomposite coatings show a conductance value of 4.1 Omega(-1) cm(-1) and 5.9 Omega(-1) cm(-1) after reducing in forming gas. Sheet resistance of ca. 1200 Omega/square with coexistent transmittance of 85% at 550 nm for a layer thickness of about 1.45 mu m was achieved. The conductance enhancement is a consequence of nanoparticulate ITO network densification due to the acting shrinkage forces caused by the polymer matrix during film drying and additionally UV-induced crosslinking of PVA. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Indium tin oxide (ITO); Nanoparticles; Polyvinyl alcohol (PVA); Polyvinyl acetate (PVAc); Polyvinyl butyral (PVB); Nanocomposite

Tuning Electrical and Optical Properties of Transparent Conductive Thin Films Using ITO and ZnO Nanoparticles, Sol-Gel-ZnO and Ag Nanowires - Schuster, Matthias; Groß, Stephanie; Roider, Florian; Maksimenko, Ilja; Wellmann, Peter (International Journal of Nanoparticles and Nanotechnology, 2017)
The progress in the research on a wet-chemical or nanoparticle derived absorber layer for solar cells leads to the fabrication of a printable transparent front electrode. This eliminates the need for vacuum technology, when the vacuum chain is already breached for the absorber deposition. The objective of this work is the manufacturing and characterization of a vacuum-free, printable, transparent front electrode on the basis of conductive metal oxides like ITO and ZnO, while reducing Indium consumption and annealing temperature or duration. Nanoparticles as well as a sol-gel process were used to deposit transparent and conductive Aluminum Doped Zinc Oxide (AZO) thin films on glass substrates. Furthermore, the influence of ion-implantation-doping after layer deposition was examined. Different temperature treatments were applied after layer deposition or ion-implantation respectively to tune the conductivity of the thin films. For characterization of the thin-films fourpoint-probe measurements, white-light-interferometry, UV/VIS spectroscopy, and (FE) SEM were used. The sol-gel-layers achieved a conductivity of 314 S/cm whereas the nanoparticle derived ZnO layers only reached 1.15 - 20 S/cm. Finally, the application of silver nanowires resulted in a low sheet resistance of 5.8 Ω/□ which is even lower than for state-of-the-art sputtered AZO-layers (15 Ω/□) and allows low annealing temperatures of only 140 °C.
Keywords: Transparent conductive film; ITO & ZnO nanoparticles; Sol-Gel ZnO:(In; Al); Silver nanowires (Ag-NW)